The temporal scale of energy maximization explains allometric variations in movement decisions of large herbivores - Daniel Fortin; Christopher F. Brooke; Hervé Fritz; Jan A. Venter (Ecosphere)
Abstract Empirical testing of energy maximization models has been used to clarify the drivers of resource partitioning among large herbivores. Most studies, however, have not considered that predictions of optimal diet depend on the temporal scale of maximization. This omission can hinder the effectiveness of optimality principles in elucidating animal distributions, dietary choices, and the dynamics of species coexistence. We used movement analysis and scale‐dependent energy gain modeling to study how three large herbivores share resources: red hartebeest (Alcelaphus buselaphus), a 120‐kg grazing ruminant; zebra (Equus quagga), a 300‐kg grazing nonruminant; and eland (Tragelaphus oryx), a 460‐kg ruminant, mixed feeder. We found that resource partitioning was achieved through a synergy of spatial segregation and interspecies differences in habitat selection and in the temporal scale of energy maximization. Radio‐collared individuals of the three species spent 95% of their time >850 m from one another. Hierarchical movement analysis revealed that red hartebeest and zebra selected grasslands within which they selected patches maximizing their daily energy gains. Selection was particularly strong for red hartebeest, as expected for a ruminant of relatively small size. Unlike the other species, eland avoided grasslands; when they ventured into grasslands, they selected patches offering high short‐term energy gains at the expense of daily gains. This selection for rapid energy gain could reflect relatively high missed opportunity costs when foraging in grasslands due to the broad range of feeding opportunities for this large mixed feeder. This finding is also consistent with the notion that larger herbivores tend to face stronger constraints from resources availability than digestibility. Overall, differences in selection strength and foraging currencies among these large herbivores are consistent with allometric theory. Our study illuminates the drivers of resource partitioning that can promote the coexistence of large herbivore species, while also showing that, to provide a useful and robust basis to explain animal movement and resource partitioning, energetic models should be based on a relevant scale of energy maximization.